Biotechnological Methods of Destruction of Chemical Warfare Agents and Their Detoxication Products - I. V. Filimonov; A. A. Yankovskaya; N. V. Zavyalova; A . N. Golipad; D. P. Kolesnikov; V. A. Kovtun; V. I. Kholstov; Ye. N. Yefremenko (Вестник войск РХБ защиты)
The work presents an overview of the main results of experimental and theoretical researches made by the Federal State Budgetary Establishment «27 Scientific Centre» of the Ministry of Defence of the Russian Federation together with other scientific organizations and institutions in 1989–2014 in the sphere of the development of biocatalysts, and biotechnological methods of destruction of chemical warfare agents (organophosphorus agents) and the products of their detoxication, including the reactionary masses, obtained during the industrial destruction of chemical weapons. The article shows that the methods of the remediation of soil and purification of water with the usage of microorganisms-destructors or their consortiums and their enzymes can be used for the neutralization of any detoxication products of chemical warfare agents, obtained by the usage of different technologies of chemical neutralization. This indicates the possibility of environmentally friendly neutralization and detoxification of considerable volume and concentrations of agents as well as large territories at the sites of former production, storage and destruction of chemical warfare agents. These eco-friendly and safe neutralization and detoxification technologies can be based on microbial biocatalytic processes. The authors assert that on the basis of the analysis mentioned above it is possible to substantiate the choice of the enzymes and the strains with high destruction ability and tolerance towards toxic agents, to elaborate the technological schemes of the production of the eco-biopreparations (biocatalysts) on the basis of the enzymes and microorganizms-destructors and to develop the technological schemes of the remediation of soil and purification of water using biocatalyst-enzymes and immobilized bacterial cells.